Microstructure evolution mechanism of tungsten induced by ultrasonic elliptical vibration cutting at atomic/nano scale - Wang, Hao; Kang, Renke; Bao, Yan; Wang, Kaixuan; Guo, Xiaoguang; Dong, Zhigang (International journal of mechanical sciences, 2023)
•Dislocation, amorphous and nanocrystal are the mechanisms of plastic deformation of tungsten.•Tungsten surface forms nanocrystals under UEVC compared with common cutting.•The instantaneous shear stress of UEVC is three times that of common cutting.•The relationship between shear stress and microstructure evolution in UEVC is given.•The microstructure evolution mechanism of tungsten induced by UEVC is revealed. Ultrasonic elliptical vibration cutting (UEVC) technology has been utilized for ultra-precision machining of difficult-to-machine metal materials such as tungsten. Nevertheless, the microstructure evolution mechanism of tungsten under the synergistic effect of ultrasonic and mechanical loads remains unclear, particularly at the atomic/nano scale. Additionally, the plastic deformation mechanism of tungsten differs from that of other metallic materials due to its low dislocation mobility (brittle at room temperature). Hence, the molecular dynamics simulation of UEVC for single crystal tungsten was established to study its mechanisms in plastic deformation and microstructure evolution under stress induction in this study. The results indicated that the main plastic deformation mechanisms including dislocation slip, amorphous phase transformation and nanocrystal were found during the tungsten removal, and accompanied by some extent of lattice distortion. The instantaneous shear stress of UEVC reached 16.88 GPa. Compared with common cutting (CC), the formation of nanocrystals mainly occurred in UEVC because the instantaneous shear stress exceeded the critical shear stress of multiple slip systems during cutting. Similarly, the high dislocation density and high plastic deformation degree of the machined zone in UEVC were also attributed to the high shear stress. The dynamic recrystallization of tungsten induced by UEVC was realized from dislocation slip to the formation of dense dislocation walls, followed by the formation of sub-grain boundaries, and finally to the formation of nanocrystals. [Display omitted]